Investigation of the effects of machining parameters and air blowing on surface topography in high speed end milling of silicon - Amin, A. K. M. Nurul; Khalid, Noor Syairah; Mohd Nasir, Siti Nurshahida; Arif, Muammer Din (Trans Tech Publications, Switzerland, 2012)
Machining of silicon is an expensive affair because its inherent brittleness leads to subsurface crack generation. Research endeavours have therefore focused on ductile mode machining of silicon to obtain crack free machined surfaces with roughness as low as 0.22 μm or even below, hence eliminating the need for subsequent polishing/grinding operations. However, most of these research works utilized expensive ultraprecision machines and tools. This research aimed at determining the viability of using conventional milling machines with diamond coated tools, high speed attachments, and air blowing mechanisms in order to achieve ductile regime machining of silicon. Spindle speed, depth of cut, and feed rate, ranges: 60,000 to 80,000 rpm, 10 to 20 μm, and 5 to 15 mm/min respectively, were considered as the independent machining parameters. Compressed air at 0.35 MPa was also provided to prevent chip deposition on the finished surfaces. The resultant surfaces were analysed using Optical and Scanning Electron Microscopes. Then, the influence of each machining parameter on surface roughness was investigated. From the analyses it was concluded that all three machining parameters and air blowing had significant influence on the surface topography and integrity of silicon.